Topiramate-Induced Valproate Toxicity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Three children with severe refractory epilepsy who developed typical valproate (VPA) adverse effects after introducing topiramate (TPM) in combination are reported from the University of Mannheim, Germany.